Typical Lung Carcinoids with Metastasis: Potential Role of MicroRNAs in the Regulation of Adaptive Immunity Associated with Disease: a Case Study - Seneda, Ana L. [UNESP]; Lapa, Rainer M Lopez; Felix, Tainara F. [UNESP]; Minutentag, Iael W. [UNESP]; Campos, Carolina F. [UNESP]; Oliveira, Rogério A de [UNESP]; Oliveira, Cristiano C. [UNESP]; Hasimoto, Érica N [UNESP]; Cataneo, Daniele C. [UNESP]; Cataneo, Antonio J M [UNESP]; De Faveri, Julio [UNESP]; Drigo, Sandra A. [UNESP]; et al. (Cell Physiol Biochem Press, 2021)
BACKGROUND/AIMS: Lung carcinoids are uncommon neuroendocrine tumours. Molecular features of lung carcinoids have been poorly defined. microRNAs (miRNAs) are potent gene expression regulators with important roles in cancer development and progression. However, little is known on the role of miRNAs in the pathogenesis of lung carcinoids. Our goals were to identify commonly deregulated miRNAs in a rare case of lung carcinoid of typical histology with metastasis, as well as map miRNA target genes in pathways potentially associated with disease development and progression. METHODS: miRNA expression profiles were assessed using the TaqMan Low Density Arrays, which is a platform including 384 miRNAs. miRNA profiles were generated in the tumor and its corresponding lymph node metastasis, compared to reference normal lung tissues. Furthermore, miRNA expression was validated in a separate, publicly available external dataset (n=19 typical lung carcinoids; 2/19 were metastatic tumors, compared to six normal lung tissues, GSE77380). Following this analysis, computational tools were applied for data interpretation. miRTarBase was used to determine miRNA-target genes, followed by ToppGene Suite analysis to identify pathways and biological functions. In addition, the expression of genes targeted by miRNAs was validated in a second, separate external dataset (n=13 tumour samples, GSE35679). GEO2R data analysis tool was used in both validation analyses (miRNAs and genes). RESULTS: We identified 15 commonly significantly downregulated miRNAs (fold change, FC≥2 and p<0.05) in the tumour and its paired metastasis, with further decreasing levels in the metastatic lesion. Downregulation of miR-126-3p and miR-146b-5p was validated in the external dataset GSE77380. In addition, SOX2 and TCF4 genes, targeted by miR-126-3p, were consistently overexpressed in a subset of six typical lung carcinoids from the external dataset GSE35679. Pathways analysis showed that miRNAs miR-126-3p and miR-146b-5p target genes with a role in the regulation of adaptive immune response. CONCLUSION: Our results contribute to the identification of miRNA expression changes in a typical lung carcinoid and its corresponding lymph node metastasis. Down-regulated levels of miR-126-3p and miR-146b-5p and target gene over-expression could play a role in the progression of this case of primary typical lung carcinoid to regional metastasis. Identified miRNAs and target genes are potential candidates for validation in a larger number of cases.
Keywords: Lung carcinoid; MicroRNAs; Immune system; Disease progression; Metastasis